Indigenous voices: Using cultural knowledge for tourism - Schmider, Joann; Prideaux, Bruce; Fredericks, Bronwyn (Annals of tourism research empirical insights, 2024)
This research reports on Indigenous cultural knowledge holders' opportunities and challenges in using their cultural knowledge to develop authentic tourism experiences. The research investigated issues related to sourcing, storing, managing, and authorising local cultural knowledge to create authentic tourism experiences. The key finding is that while Aboriginal parties are interested in using cultural knowledge to develop tourism products, pathways need to be designed to facilitate the related development. The research utilised the Indigenous research yarning method and found this approach to be particularly useful with potential for broader use in qualitative research. The findings can be applied more broadly across the Australian national tourism landscape. The findings advance knowledge management theory through the lens of Indigenous tourism. •Indigenous cultural knowledge assets for developing Indigenous tourism experiences•Knowledge management tools can assist in developing Indigenous tourism•Indigenous destination images provide alternatives and add to Western presentations•Indigenous yarning is culturally appropriate for qualitative tourism research